Anterior Subluxation after Total Hip Replacement Confirmed by Radiographs: Report of Two Cases - Conor P. McGrory; Brian J. McGrory (Advances in Orthopedics)
Demonstrable anterior subluxation of the femoral head after a total hip arthroplasty is a rare complication and is usually transient. Both a case of recurrent subluxation and a case of chronic subluxation are described in this paper, each one presenting with unexpected femoral head eccentricity in the acetabulum on radiograph. We show how this unusual complication can be successfully identified and treated.